Approximation of circular arcs using quartic bezier curves with barycentric coordinates satisfying G2 data - Azhar Ahmad (N/A, 2017)
Approximation of circular arcs using quartic bezier curves with barycentric coordinates satisfying G2 data by Azhar Ahmad